1998
DOI: 10.1001/archneur.55.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction in Neurodegenerative Disease

Abstract: As expected, severe deficits were found for both patients with AD and PD in each of the 3 olfactory domains relative to controls. However, no discriminating olfactory deficits were seen between patient groups or among the 3 measured olfactory domains, suggesting a similar disturbance in olfactory function between patients with AD and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
153
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(166 citation statements)
references
References 72 publications
9
153
0
Order By: Relevance
“…This position would agree with that of central processing de®cits (commented on in the sections on pathological states) that the association between age and decreased olfactorial abilities is less a matter of physical ability to receive the sensory signals and more about decreases in ability to recognize and process those signals. Support for this notion comes from a recent meta-analysis of olfactory functioning in AD and PD (Mesholam, Moberg, Mahr, & Doty, 1998) showing similarities in olfactory disturbances among all of the neurodegenerative diseases that affect central processing abilities. By studying pathological states in aging, we have a chance of gaining insight into normative aging.…”
Section: Discussionmentioning
confidence: 99%
“…This position would agree with that of central processing de®cits (commented on in the sections on pathological states) that the association between age and decreased olfactorial abilities is less a matter of physical ability to receive the sensory signals and more about decreases in ability to recognize and process those signals. Support for this notion comes from a recent meta-analysis of olfactory functioning in AD and PD (Mesholam, Moberg, Mahr, & Doty, 1998) showing similarities in olfactory disturbances among all of the neurodegenerative diseases that affect central processing abilities. By studying pathological states in aging, we have a chance of gaining insight into normative aging.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike AD, however, CADASIL is a pure form of vascular cognitive impairment [10]. It is well known that a significant impairment in olfactory identification ability is found in a number of neurodegenerative disorders, including AD [1,2]. However, we are aware of only 3 studies that have examined the olfactory identification ability in patients with cognitive impairment of vascular origin, and these studies had conflicting results [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory identification deficits have been described in various neurodegenerative disorders, including Alzheimer’s disease (AD), idiopathic Parkinson’s disease and dementia with Lewy bodies [1,2]. Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited angiopathy caused by mutations of the Notch 3 gene on chromosome 19 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly severe olfactory disorders to those found with IPS have been observed with Alzheimer's disease (AD). Meta analysis of studies carried out up until now on olfactory disorders accompanying AD and IPS showed no differences in the test results of diagnostic use [74]. The smell disorder with AD also represents an early symptom of the disease [76].…”
Section: Smell Disorders Accompanying Neurological Illnessesmentioning
confidence: 92%
“…Huntington's disease is associated with moderate hyposmia [73]. Mild olfactory disorders have also been described for some heredoataxias and motor neuron diseases [74], [75]. Similarly severe olfactory disorders to those found with IPS have been observed with Alzheimer's disease (AD).…”
Section: Smell Disorders Accompanying Neurological Illnessesmentioning
confidence: 99%